ASSESSMENT OF SUSTAINABLE EFFICIENCY ON POTATO FARMS AT BAGHDAD GOVERNORATE - A. H. Alzubaidi; E. H. Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to evaluate the sustainable efficiency and calculate the sustainable value, opportunity cost and revenue to cost of potato production farms in Baghdad Governorate. Data were collected from a random sample of 102 spring potato producers in Baghdad governorate for the year 2022, the value-added function was estimated using three levels: economic (seeds and space), and social (education level), while environmental represented by (residual and volatile of nitrogen). Effective resources were calculated to extract the sustainability value- SV appeared on an average of 18023.15 thousand Iraqi dinars. Positive relationship with residual nitrogen and productivity, and Inverse relationship to the amount of volatile nitrogen. Whereas the average sustainable efficiency was 0.59% and has a positive relationship with productivity. The highest level of sustainable efficiency was achieved with the highest productivity of 7.4 tons/ donum, as well as residual nitrogen, where at its maximum quantity, the sustainable efficiency reached a maximum of 1.54%, although it was an inverse relationship to volatile nitrogen. The research found that, on average, the opportunity cost was 3.7 and the cost-benefit ratio was 1.09. The study concluded that as farming areas expand, the sustainable efficiency of farmers increases. It also recommended the optimal use of resources and expansion of areas to take advantage of mass production benefits. Additionally, the research emphasized the importance of using resources sustainably to avoid negative environmental impacts. This includes committing to specific dates and quantities when adding fertilizers and pesticides, as their impact on the environment is direct. Furthermore, the research highlighted the importance of participating in training courses to improve scientific knowledge and production performance.